Oral Soft Tissue Metastasis from Breast Cancer as the Only Primary Source: Systematic Review - Nausheen Aga; Ruchira Shreevats; Sonia Gupta; Harman Sandhu; Muna E.M. Hassan; Harnisha V. Prajapati (Avicenna Journal of Medicine, 2024)
Background Breast cancer is one of the most lethal neoplasms causing death. Oral cavity is the rare site of distant metastasis from breast cancer. Very little research has been conducted to date to analyze breast cancer as the sole primary source of metastasis to the oral soft tissues. The goal of this study was to examine the published cases of oral soft tissue metastasis from breast cancer as the only primary source to date.